Examine of Organizational Excellence by Corporation Performance Assessment Method; Case Study in Tikrit University - عبدالله, حاتم علي (Journal of Economics and Administrative Sciences, 2018)
The research started from the basic objective of tracking the reality of organizational excellence in educational organizations on the basis of practical application. The research in its methodology was based on the examination of organizational excellence in the way of evaluating institutional performance. Tikrit University was selected as a case study to study the reality of application to the dimensions of organizational excellence in it, The results of the analysis for ten periods during the year and month. For the accuracy of the test and its averages, it was preferable to use the T test to determine the significance of the results compared to the basic criteria.The research found that there is an organizational excellence in the University of Tikrit by 60%, mainly due to the dimensions of strategic directions and management of the process as well as financial management. The dimensions of human resources and knowledge management were not at the required level, despite the significance of the results according to test (t) With a set of recommendations that help to raise the level of excellence in the university